The skin microbiota of preterm infants and impact of diaper change frequency. - Noelle E Younge; D Joshua Parris; Daniel Hatch; Angel Barnes; Debra H Brandon (PLoS ONE)
Objective To evaluate the impact of diaper change frequency, clinical characteristics, and skin health metrics on development of the skin microbiota in preterm infants. Design A randomized controlled parallel design was used. Methods Medically stable preterm infants born <33 weeks' gestation were randomized to receive diaper changes at a frequency of every 3-hours or every 6-hours. Skin swabs were collected longitudinally from the diapered skin (buttocks) and chest. Skin pH and transepidermal water loss were measured with each sample collection. Stool samples were collected from the diaper. The microbiome at each site was characterized by 16S rRNA gene sequencing. Associations between microbiome features, diaper change frequency, and other covariates were examined using mixed effect models and redundancy analysis. Results A total of 1179 samples were collected from 46 preterm infants, beginning at a median postnatal age of 44 days and continuing through hospital discharge. Alpha-diversity of the skin microbiota increased over time, but did not differ significantly between 3-hour (n = 20) and 6-hour (n = 26) diaper change groups. Alpha-diversity of the skin microbiota was inversely correlated with skin pH, but not transepidermal water loss. Microbiota community structure differed significantly between body sites (buttocks, chest, and stool) and between individuals. Among samples collected from the diapered skin, diaper change frequency, infant diet, antibiotic exposure, and delivery mode accounted for minor proportions of the variation in microbiota community structure between samples. Relative abundances of multiple genera differed between 3- and 6-hour diaper change groups over time. Discussion/conclusion The diversity and composition of the diapered skin microbiota is dynamic over time and differs from other body sites. Multiple factors including interindividual effects, diaper change frequency, diet, and antibiotics contribute to variation in the diapered skin microbiota.